FATIGUE LIFE ANALYSIS OF THE TRIPOD SLIDING UNIVERSAL JOINT - YANG FuQin; JIANG DianBing (Jixie qiangdu)
Static analysis and fatigue analysis of the tripod sliding universal joint was conducted by Solidworks and ANSYS Workbench software. The equivalent stress distribution contour plots and fatigue life nephogram of the tripod joint was obtained, though which the fatigue damage points were found. Different sizes of fillet chamfer sizes have different lifetimes, fatigue analysis of the tripod joint with different transition arc radius indicated changing effective stress concentration size could avoid its unreasonable life distribution and improve its fatigue life.